Risk analysis of E. coli O157:H7 contamination of beef carcasses in slaughter houses in Nairobi, Kenya - Mwai, C.W.; Kang'ethe, Erastus K.; Grace, Delia; Arimi, S.M.; Makita, K. (2011)
BACKGROUND: In the year 2009, a study was carried out in abattoirs supplying meat in Nairobi, Kenya and its environs. Three slaughterhouses with different level of hygiene control, classified as export, improved and typical local, were selected. Three hundred cattle were tracked along the slaughtering process to sample faeces and carcass swabs. Faecal samples from the rectum were taken from each animal after stunning. Two carcass sites, flank and brisket were swabbed after flaying, evisceration and after cleaning. In total seven samples were taken from each carcass. METHODS: E.coli O157 was isolated by culture and serotyped using card agglutination test. The isolates were further tested for verotoxin production and Monte Carlo simulation was run to determine the risk of carcass contamination. A HACCP model was also developed for one of the abattoirs. E.coli O157:H7 was detected from the faecal and carcasses samples at different stages. RESULTS: Two hundred and eighty out of 2,100 samples (13.3%) were IMVIC positive for E. coli. (++---) and Sorbitol MacConkey negative and were therefore tentative E. coli O157 colonies. After serotyping for O157, 92 out of 280 (4.3%) isolates, were positive for E. coli O157:H7. Forty two isolates were tested for verotoxin production, eight were positive for VT1 only while two were positive for both VT1 and VT2. The probability of a carcass being contaminated with E.coli O157 in the abattoir was 2.9% (90% CI: 0.8%-6.1%), 4.8% (90%CI: 2.0%-8.6%) and 3.8% (90%CI: 1.3%-7.3%) in the export, the local improved and the typical local abattoir respectively. Based on E. coli detection as an indicator of hygiene, the risk of contamination is low in the export slaughter house followed by the typical local slaughter house and highest in the local improved; however the confidence intervals overlapped and the level of hygiene was not significantly different. This trend was observed also for the probability of a carcasses being contaminated with vero-toxin producing E. coli: 0.7% (90% CI: 0.2%-1.7%), 1.2% (90% CI: 0.4%-2.4%) and 1.0% (90% CI: 0.3%-2.0%) in the export, the local improved and the typical local abattoir, respectively. SUMMARY: This study shows that there is a risk of carcass contamination with E.coli O157 in all the different categories of slaughterhouses in Nairobi.